2013
DOI: 10.1111/jfb.12225
|View full text |Cite
|
Sign up to set email alerts
|

Does among‐population variation in burst swimming performance of sockeye salmon Oncorhynchus nerka fry reflect early life migrations?

Abstract: Using a fixed-speed test, burst swimming performance was found to vary among nine populations of emergent sockeye salmon Oncorhynchus nerka fry reared in a common-garden environment. No consistent relationship was, however, detected between difficulty of fry migration (upstream v. downstream) to rearing areas and total burst swimming duration or bursting rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…The population whereby fry swim upstream to rearing areas had higher activity levels of LDH compared to fry from a population that swim downstream (Patterson et al, 2004b). Indeed, Sopinka et al (2013) found that sockeye salmon fry from the upstream-migrating population swam for longer durations than the downstream-migrating population. Linking metabolic and swimming metrics can delineate mechanisms underlying performance, but what mechanisms underlie the observed intergenerational effects?…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…The population whereby fry swim upstream to rearing areas had higher activity levels of LDH compared to fry from a population that swim downstream (Patterson et al, 2004b). Indeed, Sopinka et al (2013) found that sockeye salmon fry from the upstream-migrating population swam for longer durations than the downstream-migrating population. Linking metabolic and swimming metrics can delineate mechanisms underlying performance, but what mechanisms underlie the observed intergenerational effects?…”
Section: Discussionmentioning
confidence: 89%
“…Offspring burst swimming capacity For a detailed description of burst swimming trials, see Sopinka et al (2013Sopinka et al ( , 2014. Approximately 1 month post-emergence, fish (n = 100 offspring reared from captive females, n = 100 offspring reared from natural migrant females) were randomly selected from their rearing trough and placed singly in a sectioned area of a flume with fixed water speed of 25 cm/s which equated to 8-8.5 fork lengths per s (mean ± SE, fork length; 2.94 ± 0.01 and 3.06 ± 0.01 cm for offspring reared from captive and natural migrant females, respectively).…”
Section: Adult Holding and Offspring Rearingmentioning
confidence: 99%
See 1 more Smart Citation
“…Once sockeye salmon fry complete yolk-sac absorption and emerge from the gravel redds, they must migrate to rearing areas (Quinn, 2005). The direction and difficulty of this migration varies between populations of sockeye salmon and therefore fry require population-specific migration strategies (Sopinka et al, 2013). Specifically, Harrison River fry must migrate downstream to the Lower Fraser River to develop in estuaries, while Chilko River fry migrate upstream to Chilko Lake, and Stellako River fry migrate downstream to develop in Fraser Lake (see Table 1, Sopinka et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…There was also significantly higher liver antioxidant capacity in Stellako River females compared to Chilko River females (z = 3.81, p b 0.01). No differences in liver antioxidant capacity was detected between Chilko River and Harrison River females (z = 0.39, p = 1.000) or Stellako River Table 1 Population-specific migration characteristics for the three study populations of Oncorhynchus nerka, including adult migration distance, elevation, effort and temperature, a description of where the rearing areas are for fry, the direction and distance fry must migrate to reach these areas from spawning grounds following emergence (Eliason et al, 2011;Sopinka et al, 2013;Whitney et al, 2013 and Harrison River females (z = 2.65, p = 0.244). Oxidative stress was highest in brain tissue of Harrison River females, which was higher than levels in Stellako (z = −4.49, p b 0.001), but not Chilko River females (z = 2.09, p = 0.3654).…”
Section: Does Maternal Oxidative Stress and Antioxidant Capacity Varymentioning
confidence: 99%